Formulasi Snack Bar Penunda Lapar Dengan Berbagai Rasio Edamame dan Biji Labu Kuning: Karakteristik Sensori dan Kadar Lemak - Muhammad Rizki Aimanulhaq; Yohana Sutiknyawati Kusuma Dewi; Lucky Hartanti (Politeknik Negeri Ketapang, 2025)
A snack bar is a bar-shaped food product designed to meet nutritional needs and serve as a snack. This study used edamame and pumpkin seeds to enhance its nutritional value. The aim of this study was to examine the sensory characteristics and fat content of hunger-delaying snack bars formulated with different ratios of edamame and pumpkin seeds. Parameters observed included color, texture, taste, aroma, overall preference, and fat content. Five formulations were used: F0 (100%; 0%), F1 (75%; 25%), F2 (50%; 50%), F3 (25%; 75%), and F4 (0%; 100%). The results showed that the formulations significantly affected color and texture, but were not significantly different in terms of taste, aroma, or overall preference. Fat content was also not significantly affected, ranging from 50.88% to 52.38%. The analysis yielded an average value for color attributes of 2.10–2.97 (slightly yellowish-brown), taste 2.73–3.07 (slightly sweet – sweet), aroma 2.27–2.93 (slightly caramel-like), texture 1.77–2.67 (not hard–slightly hard), and overall preference 3.30–3.80 (liked).